2002
DOI: 10.1023/a:1015696622961
|View full text |Cite
|
Sign up to set email alerts
|

Bolbophorus damnificus n. sp. (Digenea: Bolbophoridae) from the channel catfish Ictalurus punctatus and American white pelican Pelecanus erythrorhynchos in the USA based on life-cycle and molecular data

Abstract: The common pathogenic prodiplostomulum metacercaria in the flesh, mostly near the skin, of pond-produced channel catfish Ictalurus punctatus has been demonstrated to be Bolbophorus damnificus Overstreet & Curran n. sp. The catfish acquires the infection from the snail Planorbella trivolvis, the only known first intermediate host, and the species is perpetuated through the American white pelican Pelecanus erythrorhynchos, as confirmed by experimental infections with nestling and dewormed adult pelican specimens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
100
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(104 citation statements)
references
References 25 publications
4
100
0
Order By: Relevance
“…Overstreet et al (2002) have shown that at least some of those records represent one and in some cases two related species of Bolbophorus. Whether B. confusus, which we consider to be a European species, exists in North America still has to be determined (Overstreet et al 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overstreet et al (2002) have shown that at least some of those records represent one and in some cases two related species of Bolbophorus. Whether B. confusus, which we consider to be a European species, exists in North America still has to be determined (Overstreet et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Whether B. confusus, which we consider to be a European species, exists in North America still has to be determined (Overstreet et al 2002). One of the two species previously reported in part as B. confusus by at least some authors (e.g., reviews by Olson 1966, Overstreet et al 2002, Appendix 1) was considered as B. damnificus, and it can be readily acquired by the AWP from feeding on infected channel catfish (Ictalurus punctatus) (Overstreet et al 2002, Overstreet andCurran 2004). The other species is referred to as Bolbophorus sp.…”
Section: Discussionmentioning
confidence: 99%
“…The disease is usually caused by the metacercaria stage of several species from different digenetic trematodes genres and families (usually Diplostomidae) (Overstreet et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The life cycle of these trematodes is complex, involving a series of at least 3 hosts, thus several fish serve as intermediate host in the development of the parasite. Usually the adult parasites are located in the piscivorous bird's intestine (Overstreet et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…When an adult is unknown and a diplostomoid metacercariae lacks pseudosuckers but encysts, that digenean is referred to as Neascus (e.g. Overstreet et al 2002). The life cycle of these trematodes is complex, involving a series of at least 3 hosts with various fishes serving as a second intermediate host in the development of the parasites.…”
Section: Introductionmentioning
confidence: 99%